Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/conl.12286
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Net Use in an Artisanal East African Fishery

Abstract: Widespread, anecdotal reports of the use of bed nets designed for malaria control (“mosquito nets”) in artisanal fisheries have led to concern from health and natural resource management sectors. However, mosquito net fishing (MNF) may play an important role in the livelihoods of artisanal fishers, an aspect not yet investigated. At a coastal Kenyan site among Giriama fishers, nearly half of homesteads interviewed used mosquito nets as fishing gear, targeting juvenile fish and prawns for subsistence and sale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The overwhelming response-that destructive fishing and excessive harvests of fish were the primary cause of decline for many species-illustrated this well. This perception of mosquito nets has also been encountered in other regions of Africa and Asia (Bush et al, 2017;Short, Gurung, Rowcliffe, Hill, & Milner-Gulland, 2018), but there is no demonstrated link between their use and observed declines in fish abundance and sizes (Bush et al, 2017). Impacts of different levels and types of fishing on small-scale riverine fisheries need to be investigated along with environmental variability (Abbott & Campbell, 2009).…”
Section: Historical Experiences Of Fishery Conflicts and Lekmentioning
confidence: 99%
“…The overwhelming response-that destructive fishing and excessive harvests of fish were the primary cause of decline for many species-illustrated this well. This perception of mosquito nets has also been encountered in other regions of Africa and Asia (Bush et al, 2017;Short, Gurung, Rowcliffe, Hill, & Milner-Gulland, 2018), but there is no demonstrated link between their use and observed declines in fish abundance and sizes (Bush et al, 2017). Impacts of different levels and types of fishing on small-scale riverine fisheries need to be investigated along with environmental variability (Abbott & Campbell, 2009).…”
Section: Historical Experiences Of Fishery Conflicts and Lekmentioning
confidence: 99%
“…The ready availability of both new and used nets has been posited as a significant incentive for MNF (Short et al, 2018;Bush et al, 2016). The current WHO policy sets guidelines at a broad population level of 1 net for every 1.8 people to achieve UC.…”
Section: Objective Settingmentioning
confidence: 99%
“…The practice appears to have increased exponentially ever since and prevalence of MN fishing has recently been posited as far broader and more frequent than previously appreciated at the global level (Short et al, 2018). Although there have been numerous reports of Mosquito Net Fishing (MNF) in the media, little empirical investigation has been conducted, save for a handful of localised case studies; some of which present the issue as negligible in terms of scale and impact on anti-malarial efforts, and others which suggest it is a significant and growing problem particularly in terms of fishery sustainability (McLean et al, 2014;Bush et al, 2016;Eisele, Thwing & Keating, 2011;Minakawa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mosquito nets is a potential example of this, with consequential negative implications for human health, fisheries sustainability and ecosystem resilience. Given that mosquito nets are available either for free or at minimal cost, it provides opportunities for all members of society to efficiently harvest resources from the marine environment with minimal effort, as expensive fishing gears and vessels are no longer required (Bush et al 2017). With new entrants to the fishery, higher pressure is put on marine resources.…”
Section: Introductionmentioning
confidence: 99%